An Approach for Surfaces Using an Asymptotic Curve in Lie Group - Yoon, Dae Won; Yuzbasi, Zuhal Kucukarslan; Bektas, Mehmet (Amer Scientific Publishers, 2017)
We analyze a new method for constructing a surface family from a given curve as an asymptotic curve using the Frenet frame of the curve in a 3-dimensional Lie group G. We derive the conditions for that curve being asymptotic curve for the parametric surface. Finally, we illustrate some interesting examples to support our method.
Keywords: Lie Group; Asymptotic; Parametric Surface